2021
DOI: 10.1002/pssb.202000497
|View full text |Cite
|
Sign up to set email alerts
|

Oxide‐Based Optoelectronics

Abstract: Integrated Si photonics has the potential to revolutionize the processing of information between different integrated chips, as well as within a single chip itself. By performing at least a part of the task with photons rather than electrons, new opportunities for broad‐band low‐power communication and computing are created. Herein, the theoretical description of the linear electro‐optic (EO), or Pockels, effect and a newly elucidated design rule for materials evaluation is summarized. Possible applications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The electro-optic modulator, used to interconvert electrical and optical signals for long-haul telecommunications, uses bulk single crystals of lithium niobate (LiNbO 3 , LNO). There is significant interest in integrating optical devices into thin film form which offers benefits such as smaller devices, lower drive voltages, and integrability with photonics and optical circuitry/computing [179]. Ferroelectric materials have traditionally been considered for thin-film optics as they exhibit the electro-optic, elasto-optic, and bulk photovoltaic effects [180].…”
Section: Nonlinear Optical Effectsmentioning
confidence: 99%
“…The electro-optic modulator, used to interconvert electrical and optical signals for long-haul telecommunications, uses bulk single crystals of lithium niobate (LiNbO 3 , LNO). There is significant interest in integrating optical devices into thin film form which offers benefits such as smaller devices, lower drive voltages, and integrability with photonics and optical circuitry/computing [179]. Ferroelectric materials have traditionally been considered for thin-film optics as they exhibit the electro-optic, elasto-optic, and bulk photovoltaic effects [180].…”
Section: Nonlinear Optical Effectsmentioning
confidence: 99%
“…[ 6 ] In this context, a remarkable range of new functionalities has been revealed and established in perovskite oxides and they have started to find their way into industrial applications. [ 7,8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[6] In this context, a remarkable range of new functionalities has been revealed and established in perovskite oxides and they have started to find their way into industrial applications. [7,8] Many studies have been reported on the different synthetic strategies applied for the fabrication of oxide-based perovskites: from solution route approaches to physical vapor deposition processes. [9][10][11] Among them, metal-organic chemical vapor deposition (MOCVD) routes have been largely employed for the production of oxide materials in form of thin films, and represent one of the most flexible bottom-up approaches, where functional structures are assembled starting from well-defined building-blocks, which are fine chemicals engineered through chemical synthesis.…”
mentioning
confidence: 99%
“…monolithic integration, would enable the fabrication of emerging EO devices integrated with Si photonics. 27,28) So far, this has been demonstrated for BaTiO 3 films using molecular beam epitaxy but remains challenging considering the fabrication process and cost. 2,4,5,12) Ferroelectricity in fluorite HfO 2 -based materials was reported by Boscke et al in 2011.…”
Section: Introductionmentioning
confidence: 99%